Design and characterization of poly(glycerol-sebacate)-co-poly(caprolactone) (PGS-co-PCL) and its nanocomposites as novel biomaterials: The promising candidate for soft tissue engineering. (5th September 2020) - Rostamian, Mostafa; Kalaee, Mohammad Reza; Dehkordi, Shiva Raeisi; Panahi-Sarmad, Mahyar; Tirgar, Mahtab; Goodarzi, Vahabodin
Graphical abstract: Highlights: A new type of bio-rubber Poly(glycerol-sebacate)-co-Poly(caprolactone) (PGS-co-PCL) and also its nanocomposites were synthesized. Presence of ɛ-caprolactone in PGS backbones change viscoelastic properties of PGS-co-PCL. Frequency sweep mode of DMTA analysis revealed that two glass transition temperatures are observable for PGS-co-PCL and its nanocomposites. Dynamic contact angle showed that presence of ɛ-caprolactone in PGS changed hydrophilicity property. In-vitro study showed that PGS-co-PCL has low cell adhesion and well biocompatibility. Abstract: New biopolymers with rubber-like properties, which are prepared by green method and without using solvents, have been absorbed attention in soft tissue engineering. Residual solvents in biomaterials are as a serious drawback in against of their applications in tissue engineering field. Poly (glycerol sebacate) (PGS) is one of the elastomeric polyesters which is synthesized by poly-condensation of sebacic acid and glycerol utilizing in wide-spread applications. However, PGS needs to gain more in-depth insight into inferior properties to expand its usage in tissue engineering. In this study, a new type of biopolymer-based on Poly(glycerol-sebacate)-co-Poly(caprolactone) (PGS-co-PCL) was synthesized by the melt polycondensation method. In the following, a series of PGS-co-PCL nanocomposites containing various amounts of hydroxyapatite (HA) nanoparticles (0.5, 1 and 1.5 wt%) were fabricated through the green in-situ polymerization technique. The chemical structure and functional groups of these samples were deciphered by 1H NMR and FTIR spectroscopy. The morphology was observed via SEM and EDX-Mapping analyses. Also, the dynamic contact angle is used to identify the hydrophilicity effect of copolymerization and nanoparticles. The thermal properties were analyzed by TGA and DSC, as well as dynamic-mechanical properties by DMTA. Furthermore, hydrolytic degradation and cell adhesion are evaluated to find out the biodegradability and biocompatibility performance of PGS-co-PCL based samples in comparison to PGS. Our findings indicated that the addition of Ɛ-caprolactone section into PGS-co-PCL is a practical approach to tune the general features of PGS to make the copolymer to the promising candidate for soft tissue engineering more efficient in the presence of HA in PGS-co-PCL nanocomposites.